Writing-skills Intervention Programming and its being a Component of Response to Intervention - Michael William Dunn (Intelektual Pustaka Media Utama, 2014)
For a struggling writer, step-by-step instruction can be a helpful means to manage organizing and producing elaborate text. This mixed-methods project offered four struggling writers a mnemonic strategy called Ask, Reflect, Text (ART) in 45-minute sessions over 22 days. The second- and fourth-grade students attended a public school in the US Pacific Northwest. As a parallel component to the project, the students’ teachers and intervention specialist met with the author for 4 one-hour sessions to discuss: 1) the children’s intervention programming and progress, and 2) the paradigm of response to intervention (RTI) and their thoughts about its feasibility in classrooms. The end-of-project assessment data demonstrated that the children made progress with writing skills, but the teachers and intervention specialist felt that support personnel would be needed to manage RTI-type intervention programming in general education classrooms.